The association of dietary pattern with the risk of common chronic diseases in Shandong Province, China: a cross-sectional study - Xi Wu; Jianwei Liu; Xinyue Li; Wanxin Zhang; Yong Yang; Jiazi Ma; Mao Cao; Mengjie Cheng; Guangjian Wu; Haidi Xiu; Zhongjun Du (Frontiers in Public Health)
BackgroundChronic diseases have emerged as a significant public health challenge, impacting the well-being of the Chinese populace, despite scant research exploring the influence of dietary factors on these conditions. This article aimed to investigate the dietary patterns of adult residents in Shandong Province, China, and explore the relationship between these dietary patterns and common chronic diseases.MethodsWe used data from the Total Diet Study of the Population of Shandong Province in China between 2015 and 2016. After further screening, a total of 2,828 adult residents with complete dietary and chronic disease prevalence information were included in this study. Food frequency questionnaires were used to ascertain dietary consumption. Dietary patterns were derived through factor analysis. Multivariate logistic regression models were employed to assess the associations between dietary patterns and the risk of common chronic diseases, while adjusting for potential confounders.ResultsThree dietary patterns were identified: dietary pattern 1 (characterized by high intake of grains and tubers, vegetables, fruits, eggs, meat, nuts, and legumes); dietary pattern 2 (with high consumption of edible fungi and algae, legumes, snacks, aquatic products, and vegetables, but low in eggs); and dietary pattern 3 (high in dairy, beverages, and snacks). Notably, dietary pattern 2 was associated with a decreased risk of coronary heart disease, even after adjusting for potential confounders [odds ratio (OR) = 0.25, 95% confidence interval (CI) = 0.08-0.79, P < 0.05]. A higher incidence of dyslipidemia was significantly correlated with dietary pattern 3 (OR = 2.33, 95% CI = 1.13–4.78, P < 0.05).ConclusionsOur findings demonstrated that adherence to specific dietary patterns can influence the risk of dyslipidemia and coronary heart disease. Higher adherence to dietary pattern 3 was linked to a higher risk of dyslipidemia, while dietary pattern 2 helped reduce the risk of coronary heart disease.